STRATEGI PENGEMBANGAN WISATA BAHARI DI PANTAI LOVINA KECAMATAN BULELENG KABUPATEN BULELENG - A.A.A Ribeka Martha Purwahita (Forum Manajemen STIMI Handayani Denpasar, 2015)
Marine tourism at Lovina Beach improves the tourism developmentin North Bali, with opening the jobfields, efforts to improve the welfare of society.A unique marine tourism with its dolphin should be well manage and expand thequality product of marine tourism. Improve the quality of human resource, developbetter management in the future. This study aims to analyze supported with IFASEFASmatriks and SWOT analyze. The collecting data supported by observation,interview and questionnaires. Strategy to develop product of marine tourism, themarket penetration strategy, maintain and improve the potential of tourism strategy,expand cooperation and awareness strategy are strategies to develop marine tourism at Lovina Beach.